Postmission Altruistic Identity Disruption Questionnaire (PostAID/Q): identifying humanitarian-related distress during the reintegration period following international humanitarian aid work - McCormack, Lynne; Orenstein, Andrew; Joseph, Stephen (American Psychological Association, 2016)
Psychological care of humanitarian personnel exposed to high risk environments is not standardized across the sector. Particularly, returnees experiencing re-integration distress specific to prior aid deployment, is randomly addressed. The Postmission Altruistic Identity Disruption Questionnaire (PostAID/Q), an 18-item self-report screening tool, attempts to standardize assessment of re-integration/specific distress in returnees from humanitarian deployment. When individuals, high in altruistic identity (AI), perceive invalidation or lack of support from organization, family, or society following a difficult deployment, they may experience altruistic identity disruption (AID) manifest by interrelated feelings of isolation, doubt, and self-blame. Paradoxically, AID distress can precipitate attempts to redeploy prematurely leaving any prior adverse/traumatic responses unresolved. This study compared the discriminant validity of PostAID/Q with standardized measures of distress and social support (IES-R;GHQ-12;SPS). The construct demonstrated significant predictive value, high internal consistency and significant variance over and above the other constructs. Promisingly, PostAID/Q shows utility in predicting re-integration/specific distress postmission.